Reaction path and product analysis of sodium-water chemical reactions using laser diagnostics. (5th March 2017) - Deguchi, Y.; Muranaka, R.; Kamimoto, T.; Takagi, T.; Kikuchi, S.; Kurihara, A.
Abstract: In a sodium-cooled fast reactor (SFR), liquid sodium is used as a coolant because of its excellent heat transport capability and a large safety margin to the boiling point (1153 K) at the atmospheric pressure. On the other hand, it has strong chemical reactivity with water vapor. One of the design basis accidents of the SFR is the water leakage into the liquid sodium flow caused by a breach of heat transfer tubes. Therefore, the study on sodium-water chemical reactions is of importance for safety of SFR. The purpose of this study aims to clarify the gas phase sodium-water reaction path and reaction products quantitatively. The counter-flow diffusion experiment device was employed to analyze the reaction path and reaction products using laser diagnostics. sodium (Na), sodium dimer (Na2 ), water (H2 O), sodium hydroxide (NaOH), sodium oxides (Na2 O and NaO) and hydroxyl radical (OH) were measured using Raman spectroscopy, absorption spectroscopy, photo-fragmentation spectroscopy and laser induced fluorescence in the reaction field for the sodium-water vapor, sodium-oxygen and sodium-hydrogen reaction. Based on the measurement results by absorption spectroscopy, it was revealed that the sodium-oxygen reaction was faster than that of sodium-water. It was indicated that sodium-hydrogen reaction did not react noticeably with sodium from the measurement result as well. The main product of sodium-water reaction was determined to be NaOH and the sodium oxide was not notably measured compared with NaOH from the results by photo-fragmentation spectroscopy. The sodium oxide concentration ratio to NaOH was determined 2% with standard deviation of 3%. Its reaction path was also discussed using sodium-water, sodium-oxygen and sodium-hydrogen reaction analyses.